Analysis of land use coefficients in normative valuation - Sherenhovskyi, O.; Malanchuk, M.; Volosetskyy, R. (Land Management, Cadastre and Land Monitoring, 2024)
The basic market principles of land value formation embedded in the normative land valuation and the land use coefficients were analyzed to assess their compliance with actual price-forming factors on land market. Various approaches to land taxation were examined, including a comparison of normative land valuation and mass land appraisal, with the advantages and disadvantages of each approach described. A study was conducted on land functional use coefficient (Kfu) impact in the normative land valuation within an urban areas. The rent levels of commercial and residential properties on similar land plots in urban areas were analyzed. Based on the research conducted in this work, the discrepancy of the Kfu with market conditions of land value formation was justified. A graphical visualization of land use coefficients impact on land value according to the normative valuation was constructed, using Lviv as an example, and these data were compared with the graphical visualization of W. Alonso's Bid-Rent classical theory. The feasibility of further using normative land valuation for taxation purposes was substantiated, provided that the set of coefficients is aligned with real market parameters.Keywords: normative valuation, mass appraisal, land plot, normative valuation coefficients.
Keywords: normative valuation; mass appraisal; land plot; normative valuation coefficients